Assessing the socio-economic impacts of drought in the Ebro River Basin - Pérez y Pérez, L.; Barreiro-Hurlé, J. (Spanish Journal of Agricultural Research, 2009)
Droughts can be defined as a significant reduction in water resources during a long period of time in a large spatial area which leads to negative consequences. These episodes have traditionally been regarded as an agricultural problem and thus their economic impacts have been considered limited to the rural environments. However, current water uses cover a broader scope of economic activity and water deficits generate impacts in a greater number of sectors. The specific objective of this paper is to estimate the direct and indirect economic impacts of a drought episode in the Ebro River Basin, using available statistical information within an Input-Output framework. Direct impacts are assessed for the two main sectors affected by this drought, agriculture and energy production, and with these effects, the indirect impacts on the wider economic activity are derived for the whole river basin. Results show that this climatic episode resulted in a direct gross added value loss of over Euros 482 million in the two sectors considered with an additional induced production loss of Euros 377 million. This reduction in activity resulted also in a reduction of over 11,000 jobs.